The process of Environmental Impact Assessment in the V4 countries in the field of road construction - Gałaś, Slávka; Gałaś, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The goal of the paper is to discuss the process of the Environmental Impact Assessment (EIA) in the Visegrad Group (V4) member countries in the field of road construction. Development of the road system in V4 countries was analysed in the first part of the paper and then criteria of the screening stage of the EIA resulting from the division of projects due to their environmental impact were estimated. The second part presents results of the survey carried out in V4 countries among people involved in EIA. Responses given by people who declared their activity in the field of transport were used in the paper. Differences in EIA procedures in road investments in particular V4 countries have been pointed out.